Soil nematodes in the Skaryszewki Park in Warsaw – community density and diversity in two habitats - Ilieva-Makulec, Krassimira (Studia Ecologiae et Bioethicae, 2015)
This paper deals with the soil nematode fauna in the Skaryszewski Park (Warsaw, Poland). I compared the density, the composition and structure of domination of the nematode genera, as well as the nematode trophic structure in the two typical for thepark habitats - in soil of lawns and soil of tree plantings. The results indicate that nematode communities in the soil of tree plantings were more numerous (nearly 1.5 million ind. m-2) than in the soil of lawns (600 thousand. m-2). However, the number and the diversity of the nematode genera in the soil of the lawns (26 genera, H '= 2.80) were higher than in the soil of tree plantings (22 genera, H' = 2.27). In total 33 nematode genera were found, and only 15 of them were common for the both habitats. The degree of generic similarity between the habitats was 63%. Some differences in the nematode trophic groups structure were also noticed. Although bacterial-feeding nematodes were the dominant group in both habitats, their percentage in the soil of trees was much higher than in the soil of lawns, respectively 70 and 49%. However in soil of lawns the share of plant feeders was 10 times higher than in the soil of tree plantings. On the basis of the results an attempt to assess the conditions of the soil in the two habitats was done.